Diagnosis and Therapeutic Management of Sarcoptic Mange in Rabbits - Rathod, Yashoda; Biradar, Roopali; Kasaralaikar , Vivek R. (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A total of six rabbits of either sex aged between 1-2 years were presented to the Department of Veterinary Clinical Complex of the College, Bidar with the history of intense itching, and hair loss all over the body since last 20 days. Clinical examination revealed whitish crusty lesions and alopecia on the margins of the ear pinnae, around eyes, nose and foot region with intense pruritus, and pale conjunctival mucous membranes. Deep skin scrapings from each rabbit collected from multiple sites on microscopic examination revealed the presence of Sarcoptes scabiei mites. The affected rabbits were treated with Inj. Ivermectin @ 200 µg/kg body weight S/C, Inj. Chlorpheneramine maleate @ 0.5 mg/kg BW I/M along with supportive therapy. The owner was advised for follow up therapy with oral multivitamin (Vimeral) 10 drops twice daily, with Ivermectin injection at weekly intervals. Four weeks post-treatment skin scraping examination showed absence of mites with uneventful recovery.